Konteks Ayat Al-Qur’an dengan Pendidikan: Analisis Tafsir al-Qur’an Surah At-Tahrim Ayat 6 - Hafid Rustiawan; Hasbullah (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2023)
Suroh at-tahrim is one of the suroh in the Quran, namely the 66th suroh, consisting of 12 verses, including one of the Madaniyah surahs, as well as the 6th verse, it includes the Madaniyah verse, which is marked by its khitob, that is addressed to believers. The khitob contains instructions for believers to protect themselves and their families from hell. The verbs to guard and maintain are included in the act of educating, so it is assumed that the verse of the Qur'an suroh at-tahrim verse 6 contains education.This paper aims to understand the meaning contained in the interpretation of suroh al-“At-Tahrim specifically in verse 6, in order to gain an understanding of the education contained therein. This understanding is very important considering that the Koran is a guide for humans, especially for believers, by understanding the contents contained in the verses of the Koran we will get instructions in it to practice in everyday life. and in various aspects of human life, including the field of Education.In understanding the Qur'an suroh At-Tahrim verse 6, the author uses library research to examine various interpretations of scholars, so that the primary sources are commentary books such as Ibn Katsir, Tafsir Jallain, and others, while the secondary sources are books Education science, like the work of Prof. Dr. A. Interpretation, Prof. Ramayulis, Prof. Dr. Zakiyah Darajat and Others. To understand the meaning contained in al-Qur'an suroh At-Tahrim verse 6, referring to the explanation of the commentators as the primary source, while to understand his education the author analyzes it, through the signs contained therein, both deductively and inductively.The results of the study concluded that suroh At-Tahrim verse 6 contains Allah's command to protect oneself/take care of oneself and one's family from hell. Because maintaining/maintaining is included in educational activities, the educational content contained in suroh at-tahrim verse 6 contains Allah's command that everyone educate themselves and also educate their families with the aim of avoiding hell. Educating oneself is done by obeying Allah and educating the family is done by teaching and educating them, reminding and giving wills, even by forcing them to obey Allah